“To want is the Original Being” [The Genealogy of Reason in Schelling] - Ramírez, Carlos A. (Estudios de Filosofía, 2008)
As the title well indicates, the present piece is directed to accounting for the genesis of Human Reason and this is achieved, in the first instance, through the analysis of the Idea of God, which according to Schelling, is the content of Human Reason, though because of this, He constitutes Himslef as something rational. It is precisely this rational character of God that constitutes the step from the absolute to Him, in other words, what Schelling terms the most primary form of the spirit. This search for the Genealogy of Reason is done, in the present text, in the books “Piece on Liberty” (1809) and in the different versions of “The Ages of the World” (1811-1815). In these texts there is an elaboration of the presence of German thinkers such as Kant and Fichte in Schelling ́s Thought and besides of the presence in it of concepts such as act, through which he tries to account in a better way for the so-called originary potency, that is, of wanting that which is called original being. Thus, through this analysis the conclusion is drawn that the potency is what is always thinkable which generates the thinking act. In regard to a Theory of Rationality this means the following: reason, whose ontologized form in God, spontaneously establishes itself but on a base which she has not established.